Pemberdayaan Anggota PKK di Desa Lembu dalam Membuat Kosmetik - Sri Hartini; Hartati Soetjipto; Cucun Alep Ryanto; Margareta Novian Cahyanti; Dewi Kurniasih Arum Kusuma Hastuti (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2016)
Community Service in the Village Lembu, District of Bancak on 2015/2016 focused on training the manufacture of cosmetic products. The most mothers Household of PKK’s member supplied and trained in one skill, namely the training of cosmetic products, such as soaps, lotions and others. Service activities packaged in the form of community empowerment by methods PRA (Participatory Rural Appraisal) to form the basis of a briefing about the character cosmetic products and training products manufacture. The implementation steps include the stage of awareness of materials, devices used when creating products and maturation/curing of the product before use. The practice of making cosmetic conducted in groups and each group of at least 5 people. Completeness is the continuity of the motivation for the manufacture of cosmetic products which are prepared to serve the needs of the market. From the results of development activities can be concluded that the public powerful of time management and become skilled productive use of household appliances for the production of cosmetics, and does not stutter anymore to make cosmetics with the appropriate technology. Marketing begins with consumers who come from the rural communities Lembu, then slightly extends in the District Bancak. Two excellent products that can meet the needs of the community are soaps and lotions with a sale value of Rp. 10.000/100 ml. Monitoring and evaluation of cosmetic products made in directly consultation with the campus UKSW.